Antibody Discovery: Sourcing of Monoclonal Antibody Variable Domains - R. Strohl, William (Current Drug Discovery Technologies, 2014)
Historically, antibody variable domains for therapeutic antibodies have been sourced primarily from the mouse IgG repertoire, and typically either chimerized or humanized. More recently, human antibodies from transgenic mice producing human IgG, phage display libraries, and directly from human B lymphocytes have been used more broadly as sources of antibody variable domains for therapeutic antibodies. Of the total 36 antibodies approved by major maket regulatory agencies, the variable domain sequences of 26 originate from the mouse. Of these, four are marketed as murine antibodies (of which one is a mouse-rat hybrid IgG antibody), six are mouse-human chimeric antibodies, and 16 are humanized. Ten marketed antibodies have originated from human antibody genes, three isolated from phage libraries of human antibody genes and seven from transgenic mice producing human antibodies. Five antibodies currently in clinical trials have been sourced from camelids, as well as two from non-human primates, one from rat, and one from rabbit. Additional sources of antibody variable domains that may soon find their way into the clinic are potential antibodies from sharks and chickens. Finally, the various methods for retrieval of antibodies from humans, mouse and other sources, including various display technologies and amplification directly from B cells, are described.
Keywords: mouse